On some wave breaking for the nonlinear integrable shallow water wave equations. (November 2015) - Wu, Xinglong
Abstract: Wave breaking of the water wave is important and interesting to physicists and mathematicians. In this paper, based on the conservation laws and the blow-up scenario, some new blow-up phenomena are derived for the Camassa–Holm equation and Degasperis–Procesi equation, which have attracted much attention due to their structure.